Nutritional disorders of arable crop growth in eastern Croatia - Kovačević, Vlado (Acta Agraria Debreceniensis, 2018)
Nutritional imbalances accompanied with growth retardation of crops at early growth stage were found since the last 40 years on certain arable lands in eastern Croatia. In this regard, phosphorus (P) deficiencies in maize and wheat were found mainly on acid soils of the western part of the region, potassium (K) deficiencies in maize, soybean on the hydromorphic neutral to alkaline calcaric drained gleysols of Sava valley lowland, while zinc (Zn) deficiencies were observed mainly in seed-maize and soybean on neutral calcaric eutric cambisols of the eastern part of the region. Cold and moist spring is factor promoting P deficiency symptoms. As oasis of normal crops existed on same arable land, comparison of plant and soil composition was possible from typical sites. P nutrition disorders were in connection with the lower P and the higher aluminum (Al) and iron (Fe) concentrations in the top of plants and the lower soil pH values. K-deficiency as result of strong K fixation and imbalances with high levels of magnesium (Mg) were the main responsible factors of low maize and soybean yields on some drained gleysols. Chlorosis incidences typical for Zn deficiency in maize and soybean were in close connection with the higher soil pH, the lower quantities of mobile Zn, here and there the higher mobile P in soil, the lower concentrations of Zn and the higher levels of Al and Fe in plants. Overcoming the above mentioned disorders and normalization of yields were achieved using ameliorative fertilization either by K or P fertilizers and in case of Zn by foliar spraying of crops with 0.75% ZnSO4 solution. Also, alleviations are possible by selection of more tolerant genotypes of field crops to specific types of nutritional disorders. From this aspect, some practical solutions were recommended for maize with reference to K nutritional problems.